A cross sectional survey on physical activity among Malaysians during the Movement Control Order (MCO) - Mohamad Diah, Nurazzura; Samsudin, Suhaiza; Elumalai, Gunathevan; Abdul Rahim, Baidruel Hairiel (2021)
Objectives: 1)To identify the characteristics & experiences of physical activities among Malaysian adults during MCO period. 2)To explore changes in physical activity during MCO period.